Analysis of software for the implementation of OSINT in the field of information security - Drozd, Maria; Nesterenko, Serhiy (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2025)
Relevance. The global modern cyberspace is characterized by a rapid increase in risks and threats to important information of government agencies, business and society. In such circumstances, open source intelligence (OSINT) is gaining importance as a tool for monitoring the information space, identifying potential threats and ensuring information security. OSINT software allows you to effectively collect, analyze and interpret data from open sources, including social networks, public databases and web resources. This facilitates timely response to cyber threats, identification of vulnerabilities and decision-making to protect information systems and critical infrastructure of the state’s information relations entities. Objective. To analyze the characteristics and capabilities of modern specialized software with a view to their effective use as open source intelligence (OSINT) tools in the context of identifying potential threats and ensuring information security of subjects of information relations. Research methods. In the process of writing this article, the author used the methods of technical analysis, comparative and descriptive approach, systematization and classification to study the functionality of OSINT tools, to predict their effectiveness and development prospects. Results. Based on the analysis, the key characteristics of software solutions such as Maltego, TheHarvester, Shodan, ZoomEye, LeakIX, Sublist3r and SubFinder are identified, their suitability for monitoring the information space, identifying risks and vulnerabilities, as well as timely response to eliminate negative consequences are assessed. Recommendations for the optimal use of these tools on modern computers are proposed, taking into account the requirements for hardware, security and process automation. Consideration of the applied aspects of OSINT use makes it possible to formulate practical recommendations for cybersecurity professionals. The analysis makes it possible to integrate the results into training programs for information security specialists. It has been established that the effectiveness of OSINT largely depends on the level of user training and his/her ability to interpret the information received. The material reviewed demonstrates the prospects for using machine learning to automate data collection and filtering processes. The author emphasizes the need to continuously update the knowledge bases and algorithms used in OSINT. The results of the study can be used to create integrated solutions to ensure the cyber resilience of organizations. Conclusions. Open source intelligence (OSINT) is based on the collection, systematization and analysis of data from publicly available sources, such as social networks, websites, public databases and media. The basis of OSINT software is the use of automated tools that allow you to efficiently process large amounts of information, detect connections between data, and identify potential threats to information security. Tools such as Maltego, TheHarvester, Shodan, ZoomEye, LeakIX, Sublist3r, and SubFinder provide tasks ranging from passive data collection to active analysis of network infrastructure, which allows identifying vulnerabilities, monitoring cyberspace, and supporting timely decision-making in the field of information security and information protection. The author classifies OSINT software by functional purpose, allocating three main categories: tools for detection, extraction and aggregation of data. A comparative analysis of such tools as Maltego, TheHarvester, Shodan, ZoomEye, LeakIX, Sublist3r and SubFinder is proposed, with the definition of their key characteristics, including compatibility with operating systems, methods of information collection, process automation and security level, which helps to choose the optimal tool for solving the problems of monitoring cyberspace and countering information threats. Promising directions for further development of OSINT software in the field of cybersecurity of the State are presented.